Cooperating to make the best use of plant genetic resources in West and Central Africa: a regional imperative - Halewood, Michael; Baidu-Forson, Joseph Jojo; Clancy, Evelyn; Vodouhe, R.S.; Bioversity International; Conseil ouest et centre africain pour la recherche et le développement agricoles (2014)
Plant genetic resources for food and agriculture are a precious heritage of the people of West and Central Africa. The region is endowed with diversified agroecosystems in which crop diversity plays an integral role by contributing to the provision of food and ecosystem services. There is a growing challenge, however, in ensuring that those resources are sustainability used and conserved for future generations. For example, in some parts of the region in situ crop diversity is threatened by a number of factors including unsustainable farming practices, changing food preferences, urbanization, and climate change. It is encouraging to note that despite these challenges, there is a growing awareness of the importance of plant genetic resources in West and Central Africa. This publication presents an overview of the collaborative efforts of key actors in the subregion over the last 10 years, from conservation programmes, to high-level regional directives, to national efforts to participate in the multilateral system of access and benefit sharing of the International Treaty on Plant Genetic Resources for Food and Agriculture. Overall, these papers make a compelling case for continued subregional (and global) cooperation to sustainably and equitably use and conserve plant genetic resources.